Identifikasi Serangga Hama Selada Hidroponik sebagai Langkah Awal Penyediaan Sayur Sehat - Rizqi Aulia Nurlaili; Safira Celia Permatasari; Listya Eka Ningtyas; Reni Ambarwati (Biotropic : The Journal of Tropical Biology, 2020)
Hydroponic agriculture in urban areas is one of urban farming, an agricultural system without using soil media that uses narrow land in urban areas and is free from the use of synthetic pesticides. This purposes of this study were to identify the species, analyze the diversity, and abundance of insects that attack lettuce on hydroponic land. The samples were collected by using the yellow pan trap, netting, and hand picking methods. Identification of insects based on morphological characteristics. Data were analyzed by the Shannon-Wiener diversity index (H) and abundance index (Di). The results showed that there were 18 species of insects belongs to 13 families that attacked hydroponic lettuce, namely the family Acrididae, Agromyzidae, Aleyrodidae, Calliphoridae, Coccinellidae, Crambidae, Dolichopodidae, Hesperiidae, Noctuidae, Pieridae, Psilidae, Stratiomyidae, and Syrphidae. The diversity of the insects was in the category medium with a diversity index value of 2,707 and the most abundant species found was Chrysodeixis chalcites 11,70%, Spodoptera litura 10,64%, and Pieris rapae 9,57%.